Analisis Tingkat Konsumsi Zat Gizi terhadap Gizi Kurang Balita di Puskesmas Jelbuk Kabupaten Jember - Nurul Aini (Health Information : Jurnal Penelitian, 2019)
Children have a wide variety of problems with regard to growth, development and nutrition. Lack of macronutrients can lead to protein-calorie malnutrition and when combined with micronutrient deficiencies can cause nutritional problems in toddlers. This study aims to analyze the level of consumption in the incidence of malnutrition among children under five at Jelbuk Health Center, Jember Regency. This research is an analytical study with an observational design using a case control approach. The population in this study were all toddlers aged 0-5 years. The sampling technique used Simple Random Sampling. The sample size is determined based on the sample size formula in the study with a case control approach, namely as many as 42 toddlers. The results showed that there was a significant effect between the level of calorie consumption (p = 0.003), the level of protein consumption (p = 0.003), the level of carbohydrate consumption (p = 0.002) and the level of fat consumption (p = 0.005) with the incidence of malnutrition among children under five. There should be coordination and efforts from regional midwives, Puskesmas and the local Health Office to increase activities related to health promotion on parenting related to the importance of nutritional intake for toddlers.